RACISMO ALGORÍTMICO E CIDADANIA DIGITAL: A INTELIGÊNCIA ARTIFICIAL COMO DESAFIO AOS DIREITOS FUNDAMENTAIS E AO PROCESSO COLETIVO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Algorithmic racism, stemming from structural racism, perpetuates inequalities and weakens democracy by undermining equal opportunities. This research demonstrates that algorithmic racism, by systemically perpetuating racial discrimination, violates fundamental collective rights, such as equality and non-discrimination, affecting the very understanding of citizenship in the digital sphere. In this context, the discussion highlights the role of collective action as a tool for holding platform developers accountable, as well as the need to implement public policies that ensure the transparency and fairness of artificial intelligence systems. The results indicate that the training of technology developers is a key element for incorporating critical perspectives on inequality and promoting social justice in system development. The hypothetical-deductive methodology was used, based on the formulation of the following research question: how does algorithmic racism, influenced by historical inequalities, affect democracy, and how can public policies act to reduce this discrimination? To answer this question, analyses of scientific articles and literature reviews were conducted.Keywords: algorithmic racism; public policies; social justice.